SEMANTICIZATION AND REMOVAL OF DIFFICULTIES AT THE PRETEXT STAGE IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE - Nigora Jumanazarovna Bozorova (Western European Studies, 2024)
The article examines the methods of semanticization and the elimination of difficulties at the pre-text stage of teaching Russian as a foreign language (RFI). The main problems that students face are not knowing the vocabulary, complex grammatical constructions and cultural realities. Effective semantic methods are described, including the use of context, visual materials, synonyms and antonyms. The importance of preparing students for successful work with text is emphasized. The research results show that using a comprehensive approach at the pre-text stage reduces language stress and improves material perception
Keywords: Russian as a foreign language; RKI; semantics; pre-text stage